Gesellschaftskritik und imaginäre Institution: Zur Aktualität von Cornelius Castoriadis - Wolf, Harald (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
The article demonstrates the topicality of Cornelius Castoridis’ work in pointing to some of its aspects which can be connected to current discussions about the role and the functions of social critique and which also show several weaknesses of this discussions. After a sketch of the development of Castoriadis’ thought, three connection points to these discussions are elucidated: the question of the conditions of the possibility and of the possibilities of a justification of critique; the concept of capitalism as a project of organization, rationalization and control, instead of a market society; and the distinctive interest in resistance and practical critique in everyday life which are interpreted as germs of a non-capitalist autonomous social institution.